Etoposide-induced apoptosis results in chromosome breaks within the AF9 gene: Its implication in chromosome rearrangement in leukaemia - Cynthia Patricia, Nicholas; Sim, S.P (Scientific Research Publishing, 2012)
Treatment with etoposide (VP-16) has been associated with translocation of the mixed lineage leukaemia (MLL) gene seen in treatment-related acute myeloid leukaemia (t-AML). Among the different partner genes, AF9 is the most common partner gene of MLL. AF9 shares similar structural element with the MLL gene. Various mechanisms of translocation have been proposed for the MLL gene, including apoptosis, particularly the apoptotic nuclease. In the current study, we show that VP-16 induced cleavage of the AF9 gene in both leukaemic cells and cultured normal blood cell. All the breakpoints were mapped within the BCR1 of the AF9 gene. AF9 cleavages in leukaemic cells were abolished by pre-treatment with caspase inhibitor (Z-DEVD-FMK), suggesting the involvement of caspase-activated DNase (CAD). The absence of AF9 cleavage in K562 cells further supported the involvement of apoptosis. However, AF9 cleavages in cultured normal blood cell were not eliminated by caspase inhibitor. The possible role of CAD and other apoptotic nucleases/effectors that could be involved in AF9 translocation are discussed.